VIOLENCE AND POLITICS IN CLANDESTINE PUBLICATIONS UNDER PINOCHET: THE ARMED WORD ON THE PATRIOTIC FRONT MANUEL RODRÍGUEZ. CHILE, 1983-1987 - Pérez Silva, Claudio (Revista de Historia Social y de las Mentalidades, 2025)
This article identifies and characterises,  through an análisis of the principal pu- blication of the Frente Patriótico Manuel Rodríguez (FPMR), “El Rodriguista”, the  political bases of the political-military  strategy of the FPMR and the key elements  that configured and guided the daily activities  of the  rodriguista militarncy during the  years, 1983-1987.  the article also tries to  explain the constitutive elements and the  form in which the political homogenisation  and identity configuration of the Rodriguista  militancy were developed, and which saw  the use of political violence as a principal form of ending the military regime.
Keywords: Political Violence; identity; Militancy; dictatorship